The Stability of Sand Waves in a Tidally-Influenced Shipping Channel, Tampa Bay, Florida - Gray, John Willis (University of South Florida, 2018)
Tidally-influenced sandwaves are common coastal features present in various settings, including shipping channels. The main shipping channel in Tampa Bay under the Bob Graham Sunshine Skyway Bridge (a.k.a. the Skyway Bridge) contains such sandwave bedforms. Between the years 2000 and 2017, these bedforms have been surveyed with multibeam echosounders (MBES) on 21 occasions with ranging coverage and quality of returns. Surveys between 2000 and 2009 used a 300 kHz Kongsberg EM3000; surveys between 2015 and 2017 used a 400 kHz Reson Seabat 7125. For comparable surveys, bathymetry, backscatter, slope, curvature, planform curvature, and profile curvature maps were created and analyzed. Spectral analyses were completed on the same cross-section for usable surveys, providing a period and amplitude for the bedforms. Sediment samples were taken in September 2015 using a Shipek grab. The sediment samples were analyzed for grain size and carbonate content. A bottom-mounted ADCP recorded velocity data semi-continuously over the same time period. These data were analyzed in an effort to investigate the forcing mechanisms that influence the bedform morphology. Mean grain sizes in the shipping channel under the Skyway Bridge range from 0.01 ? (0.99 mm, coarse sand) to 1.55 ? (0.34 mm, medium sand). Calcium carbonate content ranges from 25% to 87%. The sediment sample site most representative of the sandwave bedforms has a mean grain size of 0.01 ? and a calcium carbonate content of 87%. The calculated mean current velocity required to initiate transport of the D50 and D84 grain size percentile of the representative sediment sample site is 0.70 m/s and 1.05 m/s, respectively. Analysis of the ADCP-recorded velocity data shows that the calculated D50 critical velocity is frequently reached by peak flood and peak ebb currents except during neap tides, while the D84 critical velocity is reached only intermittently, mostly during spring tides. Analysis of MBES backscatter shows similar spatial patterns in two larger MBES surveys in 2004 and 2015. Bathymetric analysis of the sandwaves shows consistent characteristics through time. Wave crest analysis reveals that bedforms migrate in both the ebb and flood directions. Spectral analysis shows primary wave spatial frequencies range from 0.13 m-1 to 0.22 m-1, and primary wave periods range from 4.5 m to 6.0 m. The predominant wavelength of sandwaves within the study area is about 5 m, with an average wave height of 0.47 m. The maximum wave height along the axial cross-section analyzed is 0.8 m, observed in April 2017. The sediments comprising the sandwave bedforms are likely winnowed by tidal currents resulting in larger grain size and carbonate content than other areas of the shipping channel and surrounding bay. Consistent patterns in MBES backscatter over time indicate that the sediment distribution pattern in the study area have not significantly changed. The size and shape of the bedforms in the shipping channel beneath the Skyway Bridge are have been in a quasi-dynamic equilibrium over the past 13 years. The bedforms are shown to migrate in both the ebb and flood directions despite an average faster ebb current velocity than a flood current velocity. More frequent and consistent MBES surveys as well as more continuous ADCP data availability would allow for better understanding of sediment transport via bedform migration in tidally-influenced environments.